1991
DOI: 10.1177/00220345910700050401
|View full text |Cite
|
Sign up to set email alerts
|

Refractive-index-adjustable Fillers for Visible-light-cured Dental Resin Composites: Preparation of TiO 2-SiO2 Glass Powder by the Sol-gel Process

Abstract: New fillers have been prepared for visible-light-cured (VL) dental resin composites with the refractive index adjustable to that of the resin phase. These SiO2 glass powders containing TiO2 up to 20 wt% were formed by heating to 1000 degrees C ground gels made from a mixture of Ti[OCH(CH3)2]4 and Si(OC2H5)4. With increasing TiO2 content, the refractive index of the prepared power increased linearly, while the optical transmittance at 467 nm decreased linearly. The experimentally formulated VL-cured resin compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…Suzuki et al reported a dental resin composite consisting of bis-GMA/TEGDMA and newly added TiO 2 -SiO 2 glass powder produced by a sol-gel process, 34 and showed that a larger monomer conversion was obtained by adding TiO 2 -SiO 2 glass powder. Stansbury and Antonucci reported composites consisting of bis-GMA/MBL or bis-GMA/TEGDMA/MBL.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al reported a dental resin composite consisting of bis-GMA/TEGDMA and newly added TiO 2 -SiO 2 glass powder produced by a sol-gel process, 34 and showed that a larger monomer conversion was obtained by adding TiO 2 -SiO 2 glass powder. Stansbury and Antonucci reported composites consisting of bis-GMA/MBL or bis-GMA/TEGDMA/MBL.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies-with a view to improving the limited depth of cure of composite resins-have reported on the effects of filler properties, such as filler size and filler content, on the light transmittance characteristics of composite resins [8][9][10][11][12] . In practice, different commercial composite resins incorporate various filler particles with different shapes and sizes 13) , and the difference in filler properties among products should result in different optical properties and color appearance of the restorations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in resin composites have been affected by developments in resin monomers (5-7), fillers (8)(9)(10), and filler/matrix coupling agents (11)(12)(13). The mechanical properties as well as optical properties of resin composites have been affected by modifications in filler size, morphology, and components (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%